2012
DOI: 10.5923/j.ijaf.20120206.07
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intercropping on the Performance of Maize and Cowpeas in Botswana

Abstract: A field experiment was conducted at Botswana College of Agriculture garden to investigate the effects intercropping maize and cowpeas on the performance of maize and co wpeas. The treat ments were sole maize crop, sole cowpea crop, intercrop 1 (spacing of 40 cm between of maize and cowpea) and intercrop 2 (spacing of 30 cm between maize and cowpea served as treatments. The experiment was monitored fro m November to March. The results show that only maize dry matter was significantly reduced by intercropping. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 32 publications
(25 reference statements)
1
12
0
2
Order By: Relevance
“…Karikari (2001) reported that intercropping maize with Bambara nut did not affect the number of cobs and weight of seed in maize. Similarly it was also reported that yield did not reduce nor increase in the intercrop of sorghum and Bambara nuts (Gabatshele et al, 2012). On the contrary, Ogah and Ogbodo (2012) reported a significant increase in total grain yield of maize when intercropped with Bambara nut than in the sole crop maize.…”
Section: Effects Of Bambara Nut Intercrop On Growth and Yield Of Maizementioning
confidence: 89%
“…Karikari (2001) reported that intercropping maize with Bambara nut did not affect the number of cobs and weight of seed in maize. Similarly it was also reported that yield did not reduce nor increase in the intercrop of sorghum and Bambara nuts (Gabatshele et al, 2012). On the contrary, Ogah and Ogbodo (2012) reported a significant increase in total grain yield of maize when intercropped with Bambara nut than in the sole crop maize.…”
Section: Effects Of Bambara Nut Intercrop On Growth and Yield Of Maizementioning
confidence: 89%
“…Bezerra et al (2008), Costa e Silva (2008) e Legwaila et al (2012) observaram os mesmos resultados para as variáveis número de grãos por vagem e peso de cem grãos, não ocorrendo diferenças significativas entre os tratamentos, indicando que os diferentes sistemas de cultivo não afetaram o processo fisiológico de formação das sementes, mantendo as características morfológicas da cultivar.…”
Section: Discussionunclassified
“…Ainda de acordo com Legwaila et al (2012), as plantas de milho no consórcio sombreiam o feijão-caupi, reduzindo a quantidade de luz necessária para estimular a produção de flores, apresentado efeito na produtividade de grãos do caupi.…”
Section: Discussionunclassified
“…There was no significant influence (P>0.05) of planting system on number of seeds per pod (table 12). Legwaila et al (2012) stated that there is no significant difference (P>0.05) in the number of seeds per pod in cowpea when intercropped with maize. Ronald (2014) reported that there was a significant difference in number of seeds per pod under 1 row Maize: 1 row cowpea intercropping pattern and sole cropping systems.…”
Section: Number Of Seeds Per Podmentioning
confidence: 99%